Literature Review on Strategies for Enhancing Human Resource Performance Among Logistics Staff - Komang Ayu Padma Dewi; Fibria Indriati (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
Logistics management within public organizations, particularly in the Indonesian National Police (Kepolisian Negara Republik Indonesia), plays a strategic role in supporting institutional operational effectiveness. The Police Logistics Staff, as a key supporting unit, faces multiple human resource management challenges, including high workloads, limited training opportunities, and performance appraisal systems that are not fully output-based. This study aims to examine strategies for improving human resource performance within the Police Logistics Staff through a literature review approach. The research employs a qualitative method with descriptive analysis of scholarly sources, books, and relevant regulations related to public sector human resource management. The findings indicate that human resource performance is influenced by several key factors, including competence, work motivation, leadership, as well as the work environment and organizational culture. Enhancing performance requires comprehensive and integrated strategies, such as needs-based training and development, motivation strengthening through reward systems, implementation of indicator-based performance management (Key Performance Indicators/KPI), utilization of technology and digitalization, and the development of adaptive and transformational leadership. In the context of the Police Logistics Staff, these strategies are highly relevant; however, their implementation faces challenges such as rigid bureaucratic structures, limited resources, and resistance to change. At the same time, opportunities arising from bureaucratic reform and digital transformation can be leveraged to improve human resource performance sustainably. This study concludes that a holistic, adaptive, and needs-based approach is essential for developing professional, effective, and accountable logistics personnel within the Indonesian National Police.